PERAN DINAS SOSIAL DALAM PENANGGULANGAN ANAK JALANAN DI KOTA BANJARMASIN - M. Ramadhani, Sarbaini Harpani Matnuh (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2016)
The method used in this study is a qualitative method. Data collected by observation, interview, and literature. In analyzing the data used qualitative analysis that includes data collection, data reduction, and data presentation. Testing the validity of the data is done by triangulation and using reference materials. The results of this study indicate that: (1) control program in the form of handling street children in terms of education: knowledge; skills; knowledge attitude that emphasizes the education of mental discipline. (2) Implementation of the program in the prevention of street children conducted with the data collected by the municipal police raids or Trantib and others and from the data subsequently used as input in penanggulanngan street children. (3) Constraints faced in tackling street children are street children who have to get back to the current coaching environment tend to live in the street and generate economic activity.How to overcome the obstacles in tackling street children among them to disseminate to the public, especially those of the motorists who move in the way that they do not give money to children who move up the road.Based on these results, it can be suggested: (1) Social Service should be able to make a new model in the management and supervision of street children in addition to provide knowledge about the dangers of drugs because street children are particularly vulnerable to the dangers of drugs. (2) The prevention of street children program implementation is maximized not only for street children netted municipal police but involving the community around. (3) In dealing with street children after getting coaching tends to return to live on the street and generate economic activity in the street should provide coaching skills that can be used by children when it will no longer be on the streets so that they can empower themselves.Keywords: Treatment, Prevention, Street Children, Social Service